Development of word booklet learning media to improve early reading ability in elementary school - Aulia Rahmadani; Nirwana Anas (Inovasi Kurikulum, 2025)
The cognitive development stages of early-grade students must begin with strengthening early reading skills as a fundamental foundation for subsequent learning. This study aims to develop a word booklet learning media that is valid, practical, and effective in improving the early reading abilities of first-grade students at SDN 014640 Sei Kepayang Tengah. The research employed a Research and Development (RnD) method using the ADDIE development model, which includes five phases: analysis, design, development, implementation, and evaluation. The study involved 16 first-grade students as research subjects. Data collection instruments included validation sheets from media, content, and language experts; pretest and posttest reading assessments; and practicality questionnaires for teachers and students. The data were analyzed using N-Gain tests and the Likert scale. The results indicate that the word booklet is highly valid, practical, and effective, with high scores across all assessment aspects. Therefore, this instructional media holds potential for sustainable use and further development through integrating technology, incorporating color, images, audio, and animated visuals that are contextually relevant to the students’ environment. This media may serve as a preventive and effective solution for continuously enhancing early reading skills among lower-grade students.   Abstrak Tahapan perkembangan kognitif pada siswa kelas awal harus dimulai dari penguatan kemampuan membaca permulaan sebagai fondasi utama dalam pembelajaran lanjutan. Penelitian ini bertujuan untuk mengembangkan media pembelajaran word booklet yang valid, praktis, dan efektif dalam meningkatkan kemampuan membaca permulaan siswa kelas I di SDN 014640 Sei Kepayang Tengah. Metode yang digunakan adalah Research and Development (RnD) dengan model pengembangan ADDIE, yang terdiri atas lima tahap: analysis, design, development, implementation, dan evaluation. Subjek penelitian melibatkan 16 siswa kelas I. Instrumen penelitian meliputi lembar validasi ahli media, ahli materi, dan ahli bahasa, serta tes kemampuan membaca (pretest dan posttest), dan angket kepraktisan untuk guru dan siswa. Data dianalisis menggunakan uji N-Gain dan skala Likert. Hasil penelitian menunjukkan bahwa media pembelajaran word booklet memenuhi kriteria sangat valid, praktis, dan efektif, dengan skor tinggi pada seluruh aspek penilaian. Oleh karena itu, media ini berpotensi digunakan secara berkelanjutan dan dikembangkan lebih lanjut melalui integrasi teknologi yang menampilkan warna, gambar, audio, serta elemen visual bergerak yang kontekstual dengan lingkungan sekitar. Media ini dapat menjadi solusi preventif dalam meningkatkan kemampuan membaca permulaan siswa kelas rendah secara berkelanjutan. Kata Kunci: booklet kata; kemampuan membaca; sekolah dasar